Association of arterial stiffness with left atrial structure and phasic function: a community-based cohort study. Issue 6 (June 2020) - Yoshida, Yuriko; Nakanishi, Koki; Daimon, Masao; Ishiwata, Jumpei; Sawada, Naoko; Hirokawa, Megumi; Kaneko, Hidehiro; Nakao, Tomoko; Mizuno, Yoshiko; Morita, Hiroyuki; Di Tullio, Marco R.; Homma, Shunichi; et al.
Abstract : Objectives: Increased arterial stiffness is currently recognized as an independent risk factor for atrial fibrillation, although the pathophysiological mechanisms remain unclear. This study aimed to investigate the association of arterial stiffness with left atrial (LA) volume and phasic function in a community-based cohort. Methods: We included 1156 participants without overt cardiovascular disease who underwent extensive cardiovascular examination. Arterial stiffness was evaluated by cardio-ankle vascular index (CAVI). Speckle-tracking echocardiography was employed to evaluate LA phasic function including reservoir, conduit, and pump strain as well as left ventricular global longitudinal strain (LVGLS). Results: CAVI was negatively correlated with reservoir and conduit strain ( r = −0.37 and −0.45, both P < 0.001), whereas weakly, but positively correlated with LA volume index and pump strain ( r = 0.12 and 0.09, both P < 0.01). In multivariable analysis, CAVI was significantly associated with reservoir and conduit strain independent of traditional cardiovascular risk factors and LV morphology and function including LVGLS (standardized β = −0.22 and −0.27, respectively, both P < 0.001), whereas there was no independent association with LA volume index and pump strain. In the categorical analysis, the abnormal CAVI (≥9.0) carried the significant risk of impaired reservoir and conduit strain (adjusted odds ratio = 2.61 and 3.73 vs. normal CAVI, both P < 0.01) in a fully adjusted model including laboratory and echocardiographic parameters. Conclusion: Arterial stiffness was independently associated with LA phasic function, even in the absence of overt cardiovascular disease, which may explain the higher incidence of atrial fibrillation in individuals with increased arterial stiffness.